DAWET BAYAT DAN POHON AREN DALAM BUSANA VINTAGE - Muna Lathifah; Toyibah Kusumawati; Suryo Tri Widodo (Style : Journal of Fashion Design, 2022)
The creation of this Final Project is titled “Dawet Bayat and Palm Trees in Vintage” is a from of ideas and appreciation developed by individuals with the aim of understanding the concept of making batik motifs by taking a dawet Bayat idea. The process and embodiment of batik works with dawet Bayat batik motif with remasol color substances, which are processed by individuals to create batik that has an aesthetic value and feelings from the author conveyed to the connoisseur of work, and as well as being the urge to keep the author. Dawet Bayat and plam trees are the art value in a work of batik motif can be channeled directly to the community, especially the people in the Bayat area. Everything is poured directly by the author into Batik art works and visual art to be a work that is acceptable to the public, and the creation of batik works that have difference from batik spread in Indonesia. The media used in fashion is the cotton cloth. This work realization process uses a method of creation that can help the process of work. Creation methods include data collection, data analysis, work designer, and labor embodiment. In the embodiment this final task, it makes 4 works, the entire collection of works is called “Dawet Wigunani” which is inspired by the Dawet Bayat and palm tree.